Integrative transcriptomic and metabolomic analysis reveals the flavor formation mechanism of green bamboo (Dendrocalamopsis oldhami) shoots - Yu Liu; Haitao Xia; Jing Li; Xin Wei; Xiaowen Li; Huanwen Xu; Jinwang Wang (Food Chemistry: Molecular Sciences)
Green bamboo (Dendrocalamopsis oldhami) represents a crucial Asian grass with medical and edible value. However, the unpalatable flavor of emerging D. oldhami bamboo shoots has reduced consumer preference. The distinct flavor of bamboo shoots could potentially be attributed to the accumulation of differential metabolites linked to variations in bamboo shoots maturation, leading to a characteristic taste. In this study, to explore the molecular mechanisms underlying the formation of the flavor characteristics in bamboo shoots, we performed a joint transcriptomic and metabolomic analysis on the principal flavor components of D. oldhami (L) and D. oldhami ‘Hualvzhu’ (HL) bamboo shoots harvested at two developmental stages, unemerged and after emerging from the soil. Physiological analysis showed that HL presented a higher water content, lower lignin content, lower flavonoids content, a lower bitterness scoring value, and a higher sucrose content compared to L. LC-MS/MS analysis identified 23,064 primary-level differential metabolites from four comparison groups, and the differential accumulation patterns of ascorbic acid and sucrose were found to cause flavor differences. GO and KEGG enrichment analysis of the transcriptomic data demonstrated that ‘Biosynthesis of secondary metabolites’ and ‘Starch and sucrose metabolism’ were the major enrichment pathways. The expression levels of GLDH, L-galDH1, and GME1 were positively correlated with ascorbic acid accumulation, whereas those of SPS1, SPP1, and SPP2 were positively correlated with sucrose accumulation. Additionally, transcription factors like AP2/ERF, NAC, and GRAS were potentially involved in the biosynthesis of ascorbic acid and sucrose. Overall, our findings firstly uncovered the flavor formation mechanism of D. oldhami bamboo shoots, offering a theoretical basis for industrial growth.